Cognitive Supervision for Robot-Assisted Minimally Invasive Laser Surgery - Fichera, Loris (Springer Theses, 2016)
Biomedical Engineering, Robotics and Automation, User Interfaces and Human Computer Interaction, Minimally Invasive Surgery